The use of blogs and discussion boards as supplementary materials to improve the writing skills in the EFL students enrolled in Reading and Writing IV at on- site system at UTPL. - Quezada Sarmiento, Pablo Alejandro (2012)
This study addresses the following topic: The use of blogs and discussion boards as supplementary material to improve the writing skills of the EFL students enrolled in Reading and Writing IV in the on-site system at UTPL. The research aim was to determine if the use of blogs and discussion boards facilitated the improvement of writing skills. This research project began by reading all the relevant literature regarding the topic of this study. Qualitative and quantitative methods were used to collect the data. The data obtained was organized in tables, per variables and indicators. In addition, a survey was used in order to ask students their opinions about the use of blogs and discussion boards in the process of improving the writing skills. This investigation took place in Universidad Técnica Particular de Loja. The project was directed towards English students enrolled in Reading and Writing IV with an average age between 19-20 years old. All of the students had Intermediate English Level. In this study it was seen that the students who used blogs and discussion boards have not improvement their writing skills significantly.